The Relationship of Self Confidence Level with Bow Modification Tools - Andrian Alga Fiki; Akhmad Sobarna; Rony Mohamad Rizal (Journal of Physical and Outdoor Education, 2026)
This study aims to determine the participants self-confidence levels and evaluate the effectiveness of interventions using bow modifications in improving archery competence. The study population was participants in the Cimahi Mandıri archery 1 training program, with a sample of 7 respondents selected using purposive sampling. Data collection instruments included a self-confidence score questionnaire, an archery score test, and observations of bow modifications. Data Were analyzed using descriptive statistics to determine the distribution of self Confidence scores and improvements in archery performance, and correlations between variables were conducted. The results showed that the majority of participants (89,1%) had self-confidence score of 21.in the moderate to low category. After the intervention, there was a significant improvement in archery skills, with bow modifications proving effective. The conclusion is that the intervention had a positive effect on improving both self-confidence and archery performance, although there were technical challenges that needed to be addressed. Recommendations are directed at improving instruments and training implementation to optimize learning outcomes.